2013
DOI: 10.3126/ijasbt.v1i1.7920
|View full text |Cite
|
Sign up to set email alerts
|

Algae of Itahari Municipality and its adjoining area, Eastern Nepal

Abstract: A total fifty-two algal taxa belonging to 3 classes and 21 families were reported from Itahari and its adjoining areas. Among them, Chlorophycean taxa were rich with 36 taxa followed by 9 taxa of Cyanophyceae and 7 taxa of Bacillariophyceae. Sixteen taxa were identified up to generic level only and rest 36 up to species level. Most of the species were collected from aquatic habitat both lotic and lentic, some were from soil and few as epiphytic. Out of 36, ten algae viz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Rai (2011a) studied algal flora of Betana wetland, Morang and reported 23 taxa including 6 diatoms which were new for the country. Similarly, Shrestha et al (2013) had studied algae of Itahari and its adjoining area and reported 52 taxa. Rai (2013Rai ( , 2014 also studied the algal flora including desmids of Koshi Tappu Wildlife Reserve.…”
Section: Methodsmentioning
confidence: 99%
“…Rai (2011a) studied algal flora of Betana wetland, Morang and reported 23 taxa including 6 diatoms which were new for the country. Similarly, Shrestha et al (2013) had studied algae of Itahari and its adjoining area and reported 52 taxa. Rai (2013Rai ( , 2014 also studied the algal flora including desmids of Koshi Tappu Wildlife Reserve.…”
Section: Methodsmentioning
confidence: 99%
“…often changes the composition of species or diversity [5]. Recently, algae have been used as healthy foods, bioenergy, organic fertilizers for plants, and for producing antibiotics like the biosynthesis of silver nanoparticles, which is considered as a nano-drug against human pathogenic microbes [6]. Algae can grow in different locations and can be distributed in any ecosystem [7].…”
Section: Introductionmentioning
confidence: 99%
“…Dahal and Jüttner (2004) have studied the water quality of middle hill springs using diatoms. Shrestha (2005) recorded 7 diatoms from Itahari and its adjoining area. Simkhada (2006) has studied the diatoms as the indicator of environmental change in lakes and ponds of low land, middle hills and high Himalaya of Nepal and concluded that the species richness was highest in Kathmandu (i.e., 213 species) in contrast to Koshi Tappu (i.e., 119 species) and high altitude lakes (i.e., 77 species).…”
Section: Introductionmentioning
confidence: 99%
“…Ghimire et al (2012) have studied diatoms from Sagarmatha National Park, Solukhumbu; Lukla to Everest Base Camp recorded 22 species of diatom. Shrestha et al (2013) have studied the algal flora of Itahari and its adjoining area recorded 4 species. This is the preliminary work for this pond as diatom flora of Hasina wetland has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%